2022
DOI: 10.21037/apm-21-3736
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effect of using percutaneous pedicle screw internal fixation for thoracolumbar fractures

Abstract: Background: Thoracolumbar fractures are common in routine injuries. The best way to treat a thoracolumbar fracture is to repair the thoracic fracture with fixation, which is classified into percutaneous pedicle screw fixation and open pedicle screw fixation. Methods:The literature was searched in the English database PubMed, Ovid-Medline, Embase, and China Biology Medicine Disc (CBM) from the date of establishment of PubMed to June 2021, and keywords such as percutaneous pedicle screw and posterior percutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Several studies and recently published meta-analyses reported an average Cobb's angle correction of 5.5 degrees. These studies also reported that with using percutaneous screw fixation, a significant improvement in the height of anterior body fracture and the canal compression usually occurred [15,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 88%
“…Several studies and recently published meta-analyses reported an average Cobb's angle correction of 5.5 degrees. These studies also reported that with using percutaneous screw fixation, a significant improvement in the height of anterior body fracture and the canal compression usually occurred [15,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 88%
“…This could be explained due to the low amount of studies that reported on this subject and the differences between the patient population of the studies. The included studies by Phan et al (2015) and Lu et al (2022) compared PP with PO and reported a shorter hospital stay, shorter operation time, lower infection rates and better pain scores following surgery, while maintaining similar radiographic outcome data ( Lu et al, 2022 ; Phan et al, 2015 ). However, PP requires a longer learning curve and may expose the surgeon to more radiation ( Court and Vincent, 2012 ).…”
Section: Discussionmentioning
confidence: 94%
“…Various meta-analysis and narrative reviews have been published on the treatment of traumatic thoracic and lumbar fractures of the spine ( Xu et al, 2013 ; Lu et al, 2022 ; McAnany et al, 2016 ; Phan et al, 2015 ; Yi et al, 2006 ; Hughes et al, 2021 ; Sun et al, 2017 ; Tan et al, 2019 ; Kim et al, 2015 ; Pneumaticos et al, 2013 ). However, no comprehensive up-to-date overview is available of the different surgical methods, while using quantified outcome data.…”
Section: Introductionmentioning
confidence: 99%
“…Patients experience significant muscle strain and fracture trauma during open arch root nail internal fixation surgery treatment, and plasma CK levels are significantly elevated [ 23 ]. Open arch root nail internal fixation surgical treatment requires paravertebral muscle distraction under the guidance of an automatic retractor, and paravertebral muscle ischemia is evident, which will further reduce the risk of lumbar back muscle ischemia and increase the pain level of patients [ 24 , 25 ]. The application of minimally invasive pedicle screw internal fixation can reduce the risk of denervation atrophy, the VAS score is significantly reduced, the intraoperative drainage volume and blood loss are reduced, and the patient's lumbar spine function and daily living ability are significantly restored.…”
Section: Discussionmentioning
confidence: 99%